PENGGUNAAN ALAT PERAGA TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA PADA KONSEP PERUBAHAN LINGKUNGAN DI KELAS IV SEKOLAH DASAR - Alfiati Syafrina (JURNAL FISIKA EDUKASI, 2014)
This research purpose is to find out: students in the implementation of learning activities using props, the teacher's ability to manage learning using props, presence /absence of an increase in student achievement using props to the concept of environmental changes in the fourth grade elementary school. This type of research is Classroom Action Research. Subjects in this study fourth grade students at the Cape of Good Elementary School as many as 24 people, consisting of 10 men and 14 women. Data analysis using descriptive statistics. Based on the analysis of data obtained: ( a) students in participating in learning activities using props to material changes in the environment saw an increase in cycle 1 with an average score of 64.8%, in the second cycle with an average score of 69.5%, and the third cycle with an average score of 76.3% ; (b) The ability of teachers to manage the learning environment to the material change seen an increase in cycle 1 with an average score of 4.33 with both criteria, the second cycle an average score of 4.68 with both criteria , and the average score of the third cycle 4.97 average with criteria very well and (c) Mastery of environmental change using props to get the value in cycle 1 class average 67.71, cycle II was 73.5 and the third cycle is 80. Improvement has been achieve individual success indicators and classical.